Offshore Petroleum Drilling and Production - Laik, Sukumar (Boca Raton, FL : CRC Press, 2017)
"Although the extraction of oil and gas from the bottom of the sea began more than 40 years ago, new technology has led to a rapid expansion of drilling and production in deep and ultra-deep waters, which holds the key for the oil security of any nation. This book provides comprehensive coverage of offshore oil and gas operations, including various aspects of drilling and production. It also covers offshore environments and discusses the major differences in working offshore versus onshore."--Provided by publisher.
Chapter 1 Introduction / Sukumar Laik -- chapter 2 Ocean Environment/Sea States / Sukumar Laik -- chapter 3 Offshore Drilling and Production Platforms/Units / Sukumar Laik -- chapter 4 Offshore Drilling / Sukumar Laik -- chapter 5 Offshore Well Completion / Sukumar Laik -- chapter 6 Offshore Production / Sukumar Laik -- chapter 7 Offshore Storage / Sukumar Laik -- chapter 8 Offshore Pipeline / Sukumar Laik -- chapter 9 Diving and ROV / Sukumar Laik -- chapter 10 Health, Safety and Environment / Sukumar Laik.
OCLC-licensed vendor bibliographic record.
Keywords: Offshore oil well drilling; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; TECHNOLOGY & ENGINEERING -- Civil -- General